COMPARATIVE INCOME ANALYSIS OF WAGE SYSTEM EMPING CRAFTSMAN WITH INDEPENDENT BUSINESS IN PEUKAN BARO SUB-DISTRICT, PIDIE REGENCY - Hamdani; Safrika; Julia; Bagio (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2022)
This study aims to determine the comparison of wage system emping craftsmen's income with independent businesses in Peukan Baro District, Pidie Regency. This research was conducted in Peukan Baro District, Pidie Regency, from March to May 2022. Most of the Pidie people use melinjo chips as a business, especially Peukan Baro District. All empng melinjo craftsmen are housewives who work to help the family's economy. Based on the criteria, emping craftsmen are divided into two systems, namely the wage system and the independent business system. From the two business systems, the problem is the comparison of the average income of emping craftsmen with the wage system and independent businesses. The samples of this study were 40 respondents using the wage system for chips craftsmen and 40 respondents using the self-employment system. The method in this study uses a quantitative descriptive analysis. Acceptance of emping craftsmen with a wage system of Rp. 318,500/week with a total production cost of Rp. 19,137/week. In the independent business system, the acceptance of chips craftsmen is Rp. 679,350/week and a production cost of Rp. 491,487/week. The results of the study show that there is a difference in the average income of wage system emping craftsmen and independent businesses. This can be seen from the results of the wage system emping craftsmen's income, which is Rp. 299,363/week, while in the independent business system the income is Rp. 187,863/week. It can be concluded that the income of emping craftsmen using the wage system is more profitable than the independent business system in Peukan Baro District, Pidie Regency. To see a significant difference, a table test was performed using SPSS V.21. Based on the results of the independent sample test output table test, it is known that there is a difference in the average income of wage system emping craftsmen with independent businesses seen from the Sig value. (2-tailed) of 0.00. This means that the value of Sig. (2-tailed) smaller than 0.05. This means that the value of Sig. (2-tailed) smaller than 0.05. This means that the value of Sig. (2-tailed) smaller than 0.05.